The Dynamics of Networks and Homophily - Matthew O. Jackson; Stephen M. Nei; Erik Snowberg; Leeat Yariv (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine friendships and study partnerships among university students over several years. At the aggregate level, connections increase over time, but homophily on gender and ethnicity is relatively constant across time, university residences, and different network layers. At the individual level, homophilous tendencies are persistent across time and network layers. Furthermore, we see assortativity in homophilous tendencies. There is weaker, albeit significant, homophily over malleable characteristics-risk preferences, altruism, study habits, and so on. We find little evidence of assimilation over those characteristics. We also document the nuanced impact of network connections on changes in Grade Point Average.
Keywords: D85; I21; J15; J16; Z13; 330; homophily; social networks; dynamic networks; undergraduate education; peer effects